PRESERFL MicroShunt as a treatment option for highly increased intraocular pressure in primary open angle glaucoma and pseudoexfoliation glaucoma - Theilig, Theresa; Papadimitriou, Menelaos; Meller, Daniel; Hasan, Somar (Eye, 2025)
The Preserflo-MicroShunt (PF) is an established device for treating glaucoma, effectively reducing intraocular pressure (IOP) with a good safety record. However, its efficacy in eyes with significantly elevated preoperative IOP levels is not well-documented due to exclusion from many clinical studies. This study aims to evaluate PF outcomes in eyes with highly increased IOP and compare them with those having moderately increased levels.